NAZLI ERAY'IN ÖYKÜLERİNDE YAPI VE İZLEK - ÖNAL, ŞULE YILMAZ (Fırat Üniveristesi, 2017)
Nazlı Eray, Modern Türk Edebiyatında fantastik türün önemli temsilcilerinden biridir. Öykü, roman, deneme, çocuk kitapları ve anı türlerinde eser veren yazar, öykücü kimliğiyle ön plana çıkar. Bu çalışmada Nazlı Eray'ın öykülerindeki yapısal ve izleksel unsurlar, ayrıntılı bir şekilde incelendi. Ana hatları itibariyle dört olarak düzenlediğimiz çalışmanın Birinci Bölümü'nde yazarın yaşamı, edebi kişiliği ve eserleri hakkında bilgi verildi. Yazarın hayatı hakkında bilgi verilirken yazara ait anı kitaplarından yararlanıldı. Çalışmanın İkinci Bölümü'nde yazarın sekiz adet öykü kitabı olay örgüsü, şahıs kadrosu, mekân, zaman ve bakış açısı yönünden incelendi. Öyküler bilimsel bir bakış açısıyla ve tarafsız olarak incelendi. Çalışmanın Üçüncü Bölümü'nde öykülerde yer alan izlekler incelendi. Yazarın fantastik bakış açısıyla işlenen öykülerinin merkezinde insan olduğu için öykülerde aşk, rüya, geçmiş özlemi, ölüm ve kadın izlekleri bulunur. Çalışmanın Dördüncü Bölümü'nde Nazlı Eray'ın öykülerinde kullandığı dil ve üslubu incelendi. Nazlı Eray'ın öyküleri genellikle kendi yaşamından izler taşır. Öyküler, otobiyografik bir özellik taşımasının yanı sıra kurgusal karakterleri de mitsel bir özellik gösterir. Anahtar Kelimeler: Nazlı Eray, öykü, fantastik, kurmaca, zaman, mekân, şahıs kadrosu

This paper aims to explore structural and thematic elements in the short stories of Nazlı Eary, one of the pioneers in the field of Modern Turkish Literature. She who has been very productive on many genres such as short story, novel, essay, children's books, and memoir stands out mainly with the identity of being a short story writer. The first part of this study which is aimed to consist of four parts gives information about the writer's life, literary personality , and her works. Her memoirs were quite helpful gathering information as to the writer 's real life. In the second part of the study the writer's eight short stories have been objectively and scientifically anaylsed with regard to the plot, the characters, the setting (time and location) and her viewpoint. As for the third part of the study the themes taken place in the stories have been analysed. Since the main focus of the stories which enlivened via fantastic standpoint is human beings, the stories have a diverse collection of topics related to humans including love, dream, nostalgia, death and woman. The language and the style she used in the stories have been the focus of the fourth part of the study. Short stories of Nazlı Eray generally have traces of the author's own life. Therefore the stories are not only autobiographical but also their fictional characters are mythical. The work presented here has profound implications for future studies of Nazlı Eray's short stories regarding theme and structure and may help understand the integration of fantastic and fictional genre with the name "Nazlı Eray". Keywords: Nazlı Eray, Short Story, Fantastic and Fictional Genre, The Setting (the time and location)
Structure and path in the short stories of Nazlı Eray
Keywords: Türk Dili ve Edebiyatı